1998
DOI: 10.1073/pnas.95.20.11863
|View full text |Cite
|
Sign up to set email alerts
|

The PEBP2 β MYH11 fusion created by Inv(16)(p13;q22) in myeloid leukemia impairs neutrophil maturation and contributes to granulocytic dysplasia

Abstract: Chromosomal translocations involving the genes encoding the alpha and beta subunits of the Pebp2͞Cbf transcription factor have been associated with human acute myeloid leukemia and the preleukemic condition, myelodysplasia. Inv(16)(p13;q22) fuses the gene encoding the beta subunit of Pebp2 to the MYH11 gene encoding a smooth muscle myosin heavy chain (Smmhc). To examine the effect of the inv(16)(p13;q22) on myelopoiesis, we used the hMRP8 promoter element to generate transgenic mice expressing the Pebp2␤Smmhc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…The IFP Cooperates with Arf Heterozygosity to Induce Myeloid Leukemia-Previous murine models of the inv(16) have relied on expression of the IFP coupled with mutagenesis (18,19), the removal of the Arf and p16 ink4a tumor suppressors (20), or the co-expression of oncogenes (20,21). However, only the use of chimeric mice created from embryonic stem cells containing MYH11 inserted into the CBF␤ locus, coupled with either ENU or retroviral insertional mutagenesis, has yielded an acute myeloid leukemia (18,19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IFP Cooperates with Arf Heterozygosity to Induce Myeloid Leukemia-Previous murine models of the inv(16) have relied on expression of the IFP coupled with mutagenesis (18,19), the removal of the Arf and p16 ink4a tumor suppressors (20), or the co-expression of oncogenes (20,21). However, only the use of chimeric mice created from embryonic stem cells containing MYH11 inserted into the CBF␤ locus, coupled with either ENU or retroviral insertional mutagenesis, has yielded an acute myeloid leukemia (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…Previous murine models of the inv (16) have involved the expression of the IFP coupled with either ENU mutagenesis, retroviral insertional mutagenesis (18,19), the removal of two tumor suppressors (20), or the coexpression of oncogenes (20,21). However, only the use of chimeric mice carrying a "knock-in" inv(16) allele plus random mutagenesis yielded an AML that mimicked the human disease (18,19).…”
Section: Ifp Ifp Expression Was Sufficient To Induce a Myelomonocytimentioning
confidence: 99%
“…In addition, in neutrophils from mice which express PEBP2␤/CBF␤-MYH11 as a transgene, the chimeric protein was detected in the nucleus. 31 The presence of the chimeric protein in fresh leukemic cells taken from AML-M4Eo patients has been reported previously by immunoblot analysis of whole cell lysates. 32 As for the subcellular localization of PEBP2␤/CBF␤-SMMHC in leukemic cells, there has been only one previous report.…”
Section: Discussionmentioning
confidence: 99%
“…While CBFs can act either as activators or repressors of gene expression Tanaka et al, 1995a;Kogan et al, 1998) it has been demonstrated that their activator function requires protein cofactors that bind to adjacent sites on DNA (Zaiman et al, 1996). Several in vitro transfection studies with CBFA2 fusion genes have indicated that these mutant proteins act by interfering with the activities of the normal gene product (Meyers et al, 1995b;Tanaka et al, 1995b).…”
Section: Introductionmentioning
confidence: 99%